Analysis of physical dimensions in tsunami disaster resilience in Tanjung Lesung Special Economic Zone, Indonesia - Yoanna Ristya; Hayati Sari Hasibuan; Rissalwan Habdy Lubis (Brawijaya University, 2022)
The Tanjung Lesung Special Economic Zone (SEZ) is a tourism area close to faults and active volcanoes. This location causes the Tanjung Lesung SEZ to have a high tsunami threat. In 2018, this area became an area affected by the Sunda Strait tsunami, which caused various losses, including casualties. This study aimed to examine the physical characteristics of the Tanjung Lesung coastal area, which has a tsunami threat. The physical characteristics in the research are elements that can affect the resilience of the tsunami disaster on the Tanjung Lesung coast. These include land use, topography, evacuation routes, and settlement conditions. This study used primary and secondary data obtained through government agencies and a field survey in 2021. The overlay analysis method on GIS was used to provide a spatial explanation of the physical characteristics of tsunami-prone areas. The study results showed that shrubs, a slope of 2-15%, and a height of 5-25 m above sea level dominate the area with the category of dangerous and very dangerous levels. The results also explained that there are settlements with wooden wall structures and cement floors located in very dangerous areas (with an area of 32.06 ha) and dangerous areas (with an area of 11.62 ha). Based on the analysis, there are three distinct categories in the research area. All three categories require coastal boundary planning that considers the tsunami threat to increase disaster resilience. The research results can be used to increase disaster resilience or spatial planning in coastal areas.